Traumatic Brain Injury and Stem Cell: Pathophysiology and Update on Recent Treatment Modalities. (9th August 2017) - Reis, Cesar; Gospodarev, Vadim; Reis, Haley; Wilkinson, Michael; Gaio, Josileide; Araujo, Camila; Chen, Sheng; Zhang, John H.
Abstract : Traumatic brain injury (TBI) is a complex condition that presents with a wide spectrum of clinical symptoms caused by an initial insult to the brain through an external mechanical force to the skull. In the United States alone, TBI accounts for more than 50, 000 deaths per year and is one of the leading causes of mortality among young adults in the developed world. Pathophysiology of TBI is complex and consists of acute and delayed injury. In the acute phase, brain tissue destroyed upon impact includes neurons, glia, and endothelial cells, the latter of which makes up the blood-brain barrier. In the delayed phase, "toxins" released from damaged cells set off cascades in neighboring cells eventually leading to exacerbation of primary injury. As researches further explore pathophysiology and molecular mechanisms underlying this debilitating condition, numerous potential therapeutic strategies, especially those involving stem cells, are emerging to improve recovery and possibly reverse damage. In addition to elucidating the most recent advances in the understanding of TBI pathophysiology, this review explores two primary pathways currently under investigation and are thought to yield the most viable therapeutic approach for treatment of TBI: manipulation of endogenous neural cell response and administration of exogenous stem cell therapy.